Prevalence and Incidence of Fusarium Wilt (Fusarium oxysporum f.sp. dianthi) of Carnation and its Management through Microbial Antagonists - Sharma, Savita (International Journal of Economic Plants, 2020)
In the present study, field survey was carried out in different carnation growing areas of Himachal Pradesh to record the incidence of wilt in polyhouses. During the survey of the disease, 12.9-37.35% incidence of wilt was recorded. Different soil antagonists were tested against the Fusariumwilt of carnation caused by Fusarium oxysporum f.sp. dianthi. Native fungal antagonistic species of Trichoderma viz., T. harzianum, and T. viride and four bacterial antagonists i.e. Bacillus subtilis, Brevibacillus brevis, Azotobacter chroococcum and Pseudomonas fluorescens were evaluated under in vitro conditions and all exhibited their inhibitory effect against the test pathogen. Both the species of Trichoderma were found effective against the wilt pathogen with 67.5 and 65.6% inhibition, respectively. Among bacterial antagonists, A. chroococcum was found most effective with 57.7% inhibition. In field evaluation, T. viride was found most effective among all the treatments which resulted in reduction of the incidence of carnation wilt to 14.6% in comparison to 45.3% in control.